Characteristics of water supply network zoning; Известия Томского политехнического университета [Известия ТПУ]. Инжиниринг георесурсов; Т. 335, № 2 - Sahakyan A. A. Aram (2024, 2024)
Relevance. The original studies of water supply network and network exploitation data, as well as international experience, applied in similar conditions, and the data of existing literature, data of works on water supply zoning, which were carried out in the networks of various settlements in the Republic of Armenia, have been improved and are now being implemented effectively through the clear procedure developed by us. In our case, zoning is carried out under the conditions of the existing system, therefore the methods developed during design and reconstruction work consider the features of the existing system. Aim. To develop a technique to enhance the efficiency of water supply systems by implementing network zoning. It involves transforming the network into hydraulically separated zones isolated from each other. Within each zone, water supply can be regulated based on consumption requirements. Objects. The article discusses issues related to design and reconstruction procedures of existing water supply network zones. It defines the priority of zoning implementation for the current stage and proposes a method for assessing the permissible level of losses, taking into account the technical condition of the water supply network. Methods. The calculations for this study were performed using well-known hydraulic principles and laws. Experimental studies were conducted directly on the water supply network under production conditions. Results. The actual implementation of these measures in various urban locations revealed that reduction in water usage in a service zone was only 8–10%. However, analysis of the functioning of the reconstructed zones led to the conclusion that the already constructed zones now offer suitable conditions for productive work on leak detection and elimination. In the given example, during the operation of the study zone, 4300 m (about 25%) of the existing 17400 m pipelines in the reconstruction zone were decommissioned, along with 13 of 22 pumping stations. Over two years of work, the cost of electricity at the existing yard pumping stations was reduced by more than six times, the total cost of electricity in the zone was reduced by more than twelve times, and the amount of water entering the zone was reduced by 44% as a result of the water supply system reconstruction presented in the example.